2017
DOI: 10.21660/2017.40.86187
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Susceptibility of Aedes Aegypti Larvae to Bacillus Thuringiensis Israelensis and Juvenile Hormone in Dengue Epidemic Areas of Samutsongkhram, Thailand

Abstract: Dengue hemorrhagic fever (DHF) remains one of Thailand's main public health problems. Samutsongkhram is one of the areas undergoing an epidemic of this disease. To control this disease, public health officers focus on regulating the population of Aedes aegypti larvae. The aims of this research were to study the susceptibility of Ae. aegypti to Bacillus thuringiensis israelensis (Bti) and juvenile hormone, in order to end the spread of this disease in three epidemic DHF outbreak sub-districts of Ladyai, Suanlua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…aegypti at all concentrations. These findings are in line with previous research that found this concentration could best attract mosquitoes, especially Aedes mosquitoes (Cilek et al, 2011). However, a comparison of the number of mosquitoes attracted to A. auricula-judae extract and oetenol were different at all concentrations (p > 0.05) (Figure 2).…”
Section: Efficacy Of a Auricula-judae Extract For Mosquito Attractionsupporting
confidence: 92%
See 3 more Smart Citations
“…aegypti at all concentrations. These findings are in line with previous research that found this concentration could best attract mosquitoes, especially Aedes mosquitoes (Cilek et al, 2011). However, a comparison of the number of mosquitoes attracted to A. auricula-judae extract and oetenol were different at all concentrations (p > 0.05) (Figure 2).…”
Section: Efficacy Of a Auricula-judae Extract For Mosquito Attractionsupporting
confidence: 92%
“…From all mentioned to this point, we selected Auricularia auricula-judae mushrooms as an edible and commercially available mushroom species grown in Thailand. The aim of this study was to assess larvicidal and adult mosquito attractant activity of this mushroom extract with respect to Aedes aegypti (L.) as a dengue vector and Culex sitiens Wiedemann as a filariasis and Japanese encephalitis vector (predominantly in costal habitats) (Chaiphongpachara and Sumruayphol, 2017). The results from this research revealed the ability of A. auricula-judae mushrooms to be utilized in controlling mosquitoes, leading to the creation of new additional new products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations